Benefit–cost analysis of electronic claims processing under Ghana’s National Health Insurance Scheme - Justice Nonvignon; Huihui Wang; Rebecca Addo; Anthony Seddoh (BMJ Open, 2022)
Objective The aim of this study was to evaluate the benefit–cost of E-claims. A benefit–cost analysis was used to evaluate the efficiency of E-claims from the perspective of the providers and the purchaser.Design A benefit–cost analysis approach was taken for this economic evaluation. Furthermore, we estimated the incremental benefit–cost ratio (IBCR) of the intervention under assessment.Participants Purchasers and healthcare providers of the National Health Insurance Scheme (NHIS) of Ghana were the study population.Results The analysis was stratified according to providers and purchaser. Cost incurred in processing claims electronically and manually were estimated by assessing the resource use and their corresponding costs. Sensitivity analysis was conducted to assess the robustness of the results to variations in discount rate and proportions of claims processed under E-claims compared with paper claims. The combined sample of providers and purchaser made incremental gains from processing claims electronically. The IBCR was −19.75, 25.56 and 5.10 for all (sample) providers, purchaser and both providers and purchaser, respectively. When projected for the 330 facilities submitting claims to the NHIS claims processing centre (CPC) as at December 2014, the IBCR were −35.20, 25.56 and 90.06 for all providers, purchaser and both providers and purchaser. The results were sensitive to the discount rate used and proportions of E-claims compared with paper claims.Conclusion Electronic processing of claims is more efficient compared with manual processing, hence provide an economic case for scaling it up to cover many more healthcare facilities and NHIS CPCs in the Ghana.